Decreased Expression of Intelectin 1 in the Human Airway Epithelium of Smokers Compared to Nonsmokers - Carolan, Brendan J. (2008)
Lectins are innate immune defense proteins that recognize specific bacterial cell wall components. Based on the knowledge that cigarette smoking is associated with increased risk of bacterial infections, we hypothesized that cigarette smoking may modulate the expression of lectin genes in airway epithelium. Affymetrix microarrays were used to survey expression of lectin genes in large airway epithelium from 9 nonsmokers and 20 healthy smokers and in small airway epithelium from 13 nonsmokers and 20 healthy smokers. There were no changes (>2-fold change, p<0.05) in lectin gene expression among healthy smokers compared to nonsmokers except for a striking down regulation of intelectin 1, a lectin that binds to galactofuranosyl residues in the cell walls of bacteria (large airway epithelium, p<0.01; small airway epithelium, p<0.01). This was confirmed by TaqMan RT-PCR in both large (p<0.05) and small airway epithelium (p<0.02). Immunohistochemistry assessment of airway biopsies demonstrated that intelectin 1 was expressed in secretory cells, while Western analysis confirmed the decreased expression of intelectin 1 in airway epithelium of healthy smokers compared to healthy nonsmokers (p<0.02). Finally, compared to healthy nonsmokers, intelectin 1 expression was also decreased in small airway epithelium of smokers with lone emphysema with normal spirometry (n= 13, p<0.01) and smokers with established COPD (n= 14, p<0.01). In the context that intelectin 1 is an epithelial molecule that likely plays a role in defense against bacteria, its down regulation in response to cigarette smoking is another example of the immunomodulatory effects of smoking on the immune system and may contribute to the increase in susceptibility to infections observed in smokers, including those with COPD.